2002
DOI: 10.1128/jb.184.6.1788-1793.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Active Partition GeneincCof IncP Plasmids Is Required for Stable Maintenance in a Broad Range of Hosts

Abstract: Plasmids of incompatibility group P (IncP) are capable of replication and stable inheritance in a wide variety of gram-negative bacteria. Three determinants of IncP plasmids are components of an active partition locus that is predicted to function in the segregation of plasmid copies to daughter cells. These determinants are incC, which codes for a member of the ParA family of partition ATPases; korB, which specifies a DNA-binding protein that also functions as a global transcriptional repressor; and O B , the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
2
18
1
Order By: Relevance
“…We have found that, in three alpha proteobacteria, the same localization pattern occurs, making it likely that the bacteria which support replication of a broadhost-range plasmid do so because of conserved structural elements with which they interact. These results are consistent with the function of the IncC/KorB partition system of plasmid RK2 in a variety of gram-negative bacteria including A. tumefaciens (31). It is possible that there is an even wider conservation of DNA segregation machinery, as the Soj/SpoOJ partitioning system of B. subtilis is functional in E. coli (38).…”
Section: Discussionsupporting
confidence: 77%
“…We have found that, in three alpha proteobacteria, the same localization pattern occurs, making it likely that the bacteria which support replication of a broadhost-range plasmid do so because of conserved structural elements with which they interact. These results are consistent with the function of the IncC/KorB partition system of plasmid RK2 in a variety of gram-negative bacteria including A. tumefaciens (31). It is possible that there is an even wider conservation of DNA segregation machinery, as the Soj/SpoOJ partitioning system of B. subtilis is functional in E. coli (38).…”
Section: Discussionsupporting
confidence: 77%
“…However, true par modules are absent from the IncQ plasmids. This is not due to the broad host-range of the plasmid, since RK2 has a partitioning system that is active in a number of different hosts (Siddique and Figurski, 2002). On the other hand, the IncQ2 group of plasmids (Deane and Rawlings, 2004) (Fig.…”
Section: Conclusion: the Advantages And Disadvantages Of The Rsf10mentioning
confidence: 99%
“…At least two essential processes contribute to the host range phenotype: replication and partition (42). However, replication has received more attention in the effort to understand the host range phenotype.…”
mentioning
confidence: 99%